Effectiveness of Letter Grading System in Secondary Level in the Context of Nepal - Khadka, Dambar Bahadur (Journal of Gurubaba, 2025)
Education is one of the structural backbone among all structures for the development of the nation. Skilled human resource is the key factor for national development which is possible for an effective and relevant education system in the country. This research explores the effectiveness of the letter grading system at the secondary level of education in Nepal. The traditional percentage system has been used for decades but the government of Nepal transitioned to a letter grading system to enhance educational standards. This study investigates the view of students, teachers and educational administrators regarding the letter grading system, its impact on student motivation and academic performance. A qualitative research design was employed, qualitative data. The study gathered survey data from 60 populations using structured questionnaires and conducted in-depth interviews with 15 participants. Thematic analysis of interview data helped clarify the survey findings. The main objective of this paper is to carefully explore effectiveness of the grading system at the secondary level of education in Nepal and comprehensively evaluate the contemporary grading system and conventional examination systems practiced in Nepal.The main findings reveal the effectiveness of the letter grading system and its implementation in the secondary level, counseling, and tailored support to bridge academic gaps and enhance inclusivity and it also indicates that while the letter grading system has improved clarity in evaluation and motivation among students. The research concludes that letter grading system not only fosters equity in evaluation but also enriches the learning experience by valuing diversity as a source of strength, ensuring every child feels acknowledged and empowered. The stress of the students has been reduced by taking the Secondary Education Examination (SEE), which provides students with an opportunity to pursue higher education.